Highly Localized Optical Field Enhancement at Neon Ion Sputtered Tungsten Nanotips - Paschen, Timo; Brückner, Leon; Wu, Mingjian; Spiecker, Erdmann; Hommelhoff, Peter (Nano Letters, 2023)
We present laser-driven rescattering of electrons at a nanometric protrusion (nanotip), which is fabricated with an in situ neon ion sputtering technique applied to a tungsten needle tip. Electron energy spectra obtained before and after the sputtering show rescattering features, such as a plateau and high-energy cutoff. Extracting the optical near-field enhancement in both cases, we observe a strong increase of more than 2-fold for the nanotip. Accompanying finite-difference time-domain (FDTD) simulations show a good match with the experimentally extracted near-field strengths. Additionally, high electric field localization for the nanotip is found. The combination of transmission electron microscope imaging of such nanotips and the determination of the near-field enhancement by electron rescattering represent a full characterization of the electric near-field of these intriguing electron emitters. Ultimately, nanotips as small as single nanometers can be produced, which is of utmost interest for electron diffraction experiments and low-emittance electron sources.<br